Student-Athletes Performing Community Service: Examination of Community Service Motivation and Athletic Department Involvement - Huml, Matt R.; Hancock, Meg G.; Bergman, Mathew J.; Hums, Mary A. (Social science quarterly, 2019)
Objective. For this study, we seek to examine how student-athletes’ community service is influenced by (a) their university’s athletic department and (b) student-athlete demographics. This was examined from the theoretical lens of student involvement theory (SIT). Methods. Data were collected from active student-athletes at National Collegiate Athletic Association (NCAA) Division I, II, and III institutions via an electronic survey, which collected information on community service frequency, motivations to volunteer, and athletic department involvement. Results. Student-athletes were found to perform more community service during their upperclassmen years, if they had performed community service as punishment previously in college, and if they independently chose their community service activity instead of the athletic department. Conclusions. These findings highlight both confirmation and rejection of SIT. First, results confirm SIT’s belief that students will pursue more academically related activities if they choose the activity (i.e., choosing community service venue). Contrarily, findings related to punishment reject the tenets of SIT, highlighting that athletic departments forcing of student-athletes to participate in an activity may be beneficial for their academic development.